(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The present article investigates the communicative-pragmatic and emotional functions of intonation within nonverbal discourse on the basis of English and Uzbek media reportages. In modern media communication, intonation functions not merely as a phonetic phenomenon, but also as a significant paralinguistic instrument that shapes pragmatic meaning, emotional evaluation, ideological positioning, and audience perception. The study aims to identify the similarities and differences in the use of intonation in English and Uzbek reportages and to determine how prosodic features contribute to the communicative effectiveness of journalistic speech.